2011
DOI: 10.1016/j.carbon.2011.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of carbon blacks produced by solar thermal dissociation of methane

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…Rodat et al, [11] reported that carbon black can be produced by solar methane dissociation. The other direction involved replacing the carbon black with other eco-friendly fillers such as in this research, which involved partial replacement of the carbon black with silica and fly ash.…”
Section: Carbon Blackmentioning
confidence: 99%
“…Rodat et al, [11] reported that carbon black can be produced by solar methane dissociation. The other direction involved replacing the carbon black with other eco-friendly fillers such as in this research, which involved partial replacement of the carbon black with silica and fly ash.…”
Section: Carbon Blackmentioning
confidence: 99%
“…Based on these considerations, the pilot-scale demonstration of methane splitting process in multi-tubular solar reactors (20e50 kW) was recently achieved in the range of 1400e1800 C, which produced H 2 and CB up to 2.24 Nm 3 /h (88% H 2 yield) and 330 g/h (49% C yield), respectively [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…The specific surface area (SSA) of selected soot samples (Table 5) varied in the range of 13 and 40 m 2 g -1 , which is typical to expandable graphite and graphite foils with the density of 0.3 g cm -3 [31]. The higher SSA of Run-13 refers to a more porous carbon material which is more similar to carbon black [32]. Table 5.…”
Section: Run-18 Heliummentioning
confidence: 99%